153k views
4 votes
Simplify with steps.

^^
1. (x-1)(5x+8)-2x+5
2. (-2+5)(3x+9)
3. 2x+5-8x+12
4. (-x+3)(-5x-2)

User KateLatte
by
4.3k points

1 Answer

5 votes

1. (x−1)(5x+8)−2x+5

=(x)(5x)+(x)(8)+(−1)(5x)+(−1)(8)+−2x+5

=5x2+8x+−5x+−8+−2x+5

Combine Like Terms:

=5x2+8x+−5x+−8+−2x+5

=(5x2)+(8x+−5x+−2x)+(−8+5)

=5x2 + x + −3

2. (−2+5)(3x+9)

=9x+27

3. 2x+5−8x+12

=2x+5+−8x+12

Combine Like Terms:

=2x+5+−8x+12

=(2x+−8x)+(5+12)

=−6x+17

4. (−x+3)(−5x−2)

=(−x+3)(−5x+−2)

=(−x)(−5x)+(−x)(−2)+(3)(−5x)+(3)(−2)

=5x2+2x−15x−6

=5x2 − 13x − 6

User Kvasi
by
4.5k points